Diffusion of corporate social responsibility in the airline industry. Issue 4 (12th February 2018) - Upadhaya, Bedanand; Munir, Rahat; Blount, Yvette; Su, Sophia
Abstract : Purpose: The purpose of this paper is to explore how and why corporate social responsibility (CSR) is diffused within the organisation and investigate the factors that influence the diffusion of CSR in the context of a developing country. Design/methodology/approach: Drawing on the diffusion of innovations theory, data were collected from a Nepalese airline company through semi-structured interviews supported by relevant documentary scrutiny. Findings: The findings of this study indicate that the airline company's CSR practices are aimed at enhancing organisational performance. The adoption of CSR is also seen as a proactive strategy to avoid any future risk associated with their environmental impact. The findings reveal that organisations' strategy, cultural values and beliefs and top management support are important predictors of the adoption of CSR. Practical implications: The empirical findings of this study provide valuable insights into how CSR can enhance organisations' performance if CSR is used in a strategic way. The study also highlights the important role of cultural values and beliefs in the secondary stage of adoption (or internal diffusion), as successful implementation of CSR is highly unlikely to happen without focusing on appropriate culture within the organisation. Originality/value: This study extends research on diffusion of innovations literature by focusing on both the initial and post-adoption process (primary and secondary stage of diffusion) of CSR within a single airline company operating in a developing country, Nepal.